2020
DOI: 10.3390/nu12103063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Seasoning and Cooking Fats, Arterial Stiffness and Blood Lipid Pattern in a Rural Population Sample: Data from the Brisighella Heart Study

Abstract: Background: Dietary fats have been variably associated with the risk of cardiovascular disease. The aim of our study was to evaluate the association between everyday mainly used dietary fats in cooking and as seasoning and hemodynamic and lipid parameters. Methods: For this study, we selected from the Brisighella Heart Study cohort subjects who were not treated with antihypertensive drugs and report with certainty their daily mean intake of dietary fats in cooking and as seasoning. Depending on the main source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The citizens of Brisighella are periodically solicited by educational messages on healthy lifestyle as part of the BHS; then, we might have underestimated the impact of quarantine on dietary habits of our respondents [ 18 ]. Moreover, our observations could not be directly inferred for other populations, as suggested by the results of other studies conducted in different contexts [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The citizens of Brisighella are periodically solicited by educational messages on healthy lifestyle as part of the BHS; then, we might have underestimated the impact of quarantine on dietary habits of our respondents [ 18 ]. Moreover, our observations could not be directly inferred for other populations, as suggested by the results of other studies conducted in different contexts [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study has been carried out in agreement with the Declaration of Helsinki. Its protocol—previously described elsewhere—was approved by the institutional ethical board of the University Hospital of Bologna (Code: BrixFollow-up_1972–2024) and all involved a signed informed consent form at entry from the subjects [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The survey enrolled individuals from BHS who belong to a culturally and dietary homogeneous community that may not be fully representative of the general population. In fact, the mean intake of proteins and animal saturated fats is quite elevated in this area due to the local food culture, despite some educational intervention on the general population [ 26 , 27 ]. Then, the sample size of the high-risk subgroup is relatively small, though representative of the full cohort, and consequently did not allow sub-analyses by age classes or other subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary saturated animal fats have been associated with cardiovascular risk. Prevalent vegetable oil users, especially Dietary Choices and Vascular Ageing extra-virgin olive oil and corn oil, have lower arterial stiffness compared to prevalent animal fat users in a study including the Brisighella Heart Study cohort subjects, besides lower body mass index, visceral adiposity index, blood pressure, and cholesterol level [45]. Not all studies reported endothelial dysfunction and increased arterial stiffness due to saturated fatty acids [46].…”
Section: Fatsmentioning
confidence: 99%